Magnetic resonance imaging findings in acute pulmonary embolism - Hochhegger, Bruno; Ley-Zaporozhan, Julia; Marchiori, E.; Irion, K.; Soares Souza, A.; Moreira, J.; Kauczor, Hans-Ulrich; Ley, Sebastian (British journal of radiology, 2011)
Pulmonary embolism (PE) is the third most common acute cardiovascular disease after myocardial infarction and stroke, and results in thousands of deaths each year. Improvements in MRI accuracy are ongoing with the use of parallel imaging for angiography techniques and pulmonary perfusion. This, associated with other potential advantages of MRI (e.g. a radiation free method and better safety profile of MR contrast media), reinforces its use. The aim of this paper is to perform a pictorial review of the principal findings of MRI in acute PE. Acute PE can manifest itself as complete arterial occlusion and the affected artery may be enlarged. We report the main vascular and parenchymal signs, and an overview of current literature regarding accuracy, limitations and technical aspects is provided.
Elektronische Reproduktion der Druckausgabe
Gesehen am 12.09.2022